Sensitivity Analysis of Factors Affecting Time-Dependent Slope Stability under Freeze-Thaw Cycles. (4th June 2018) - Chang, Zhiguo; Cai, Qingxiang; Ma, Li; Han, Liu
Abstract : With open-pit mines excavated, the slopes will be exposed to the natural environment for a long time. Affected by factors like temperature, seepage, mining, freeze-thaw, etc., slope structural integrity and strength will gradually decline as slope exposure time extends. Besides, the development of defect structure within the rocks is closely correlated with time. In this paper, freeze-thaw cycle tests were conducted on the saturated sandstones collected from a certain open-pit mine. According to the test results, the mass density and longitudinal wave velocity gradually increased with more times of freeze-thaw cycles while mechanical properties such as internal friction angle, cohesion, elastic modulus, and uniaxial compressive strength decreased instead. The constitutive model of saturated rock deterioration was established by taking the volume of phase transition of water in microcracks as a variable. Based on the tests results and theoretical analysis, the sensitivity of the factors affecting slope stability under freeze-thaw damage was studied by Control Variable Method (CVM) and Orthogonal Design Method (ODM). It was determined that the internal friction angle and cohesion had a highly significant effect on the test results, while the mass density had a significant effect. The conclusions may play a certain role in guiding slope construction and protection.